Trotskysm in George Orwell’s Animal Farm - yono, Hari (Faculty of Letters, Dr. Soetomo University, 2018)
Abstract: This paper presents the idea of Trostksyms in George Orwell’s Animal Farm. While critics often portray Orwell as anti- communist due to his critiques on the character Napoleon as the representation of Stalin. On the other hand, this paper describes that Orwell through the character Snowball shows great sympathy on Snowball. This paper describes that Snowball is the portrayal of Trostky.